Targeted Drug Delivery and Theranostic Strategies in Malignant Lymphomas - Etrych, Tomas; Braunova, Alena; Zogala, David; Lambert, Lukas; Renesova, Nicol; Klener, Pavel (Cancers, 2022)
Malignant lymphomas represent the most common type of hematologic malignancies. The first clinically approved TDD modalities in lymphoma patients were anti-CD20 radioimmunoconjugates (RIT) 131I-tositumomab and 90Y-ibritumomab-tiuxetan. The later clinical success of the first approved antibody-drug conjugate (ADC) for the treatment of lymphomas, anti-CD30 brentuximab vedotin, paved the path for the preclinical development and clinical testing of several other ADCs, including polatuzumab vedotin and loncastuximab tesirine. Other modalities of TDD are based on new formulations of "old" cytostatic agents and their passive trapping in the lymphoma tissue by means of the enhanced permeability and retention (EPR) effect. Currently, the diagnostic and restaging procedures in aggressive lymphomas are based on nuclear imaging, namely PET. A theranostic approach that combines diagnostic or restaging lymphoma imaging with targeted treatment represents an appealing innovative strategy in personalized medicine. The future of theranostics will require not only the capability to provide suitable disease-specific molecular probes but also expertise on big data processing and evaluation. Here, we review the concept of targeted drug delivery in malignant lymphomas from RIT and ADC to a wide array of passively and actively targeted nano-sized investigational agents. We also discuss the future of molecular imaging with special focus on monoclonal antibody-based and monoclonal antibody-derived theranostic strategies.